PERAN IBU SEBAGAI ORANGTUA TUNGGAL DALAM KELUARGA DI DESA KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Gusmira, Like; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The family is the smallest unit or institution in the midst of the community, the family generally consists of father, mother and child, but there are also families that only have mothers and children, of which mothers are single parents in a family or more known as single parent. This study aims to determine the characteristics of single parent families and the implementation of single parent family functions. The method of this research is qualitative, the sample in this study are six single parent people in Kopah Village, Kuantan Tengah District, Kuantan Singingi Regency. The results of this study indicate that the family characteristics of the six subjects in this study had a good relationship between mothers and their children. Even effective communication between parents and children is established, harmonious relationships are established between their children, mingling with the community, and carrying out religious orders properly. The six subjects in this study also succeeded in carrying out the socialization function to shape behavioral patterns, attitudes, ideals and values in society. The function of (affection) is carried out well, that is, all subjects give affection to their children, especially a mother who has an affection for all time. Likewise with the protection function (protection) all subjects in this study always provide protection to their children. For economic functions to run well, because, all subjects are able to meet their daily needs and even enough to fulfill the family's economy.Â Keywords: Role, Mother, Single Parents, Characteristics, Family Function